The Role of Planning Budgets in Financial Control of Industrial Firms ( AField Study on the Rabak Cement Company Ltd ) - األستاذ المساعد الدکتور هيثم يعقوب إسحاق عبد اه (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
The problem of the study was to identify the role of planning budgets in achieving financial control in industrial companies. The study identified Rabak Cement Company as a model for the study to identify the extent of the awareness of the financial management of Rabak Cement Company for the importance of preparing the planning budgets and proper application of these budgets according to scientific fundamentals and the greatest attention to the outputs and results of the implementation of planning budgets to avoid the occurrence of deviations in the coming years and to evaluate the performance of the company as well as to know the obstacles facing the preparation and implementation of planning budgets and to address them in the future, lies the importance of this scientific study in the most important results of the study are that Rabak Cement Company understands the importance of planning budgets and the advantages it provides. The planning budgets in the company are scientifically correct and the administration uses it. The results of the planning budgets to serve the objectives of financial control, as recommended by the study and the need to pay attention to the deviations when they occur and address them immediately and apply the results in the future as well as the need to pay attention to the budget in the implementation avoid distractions and the need for attention to deviations when they occur and address an immediate application of the results in the future and the need to replace the budget figures to convince all those on the implementation.